Efficient communication in VANET - Sharma, Shilpa; Kaur, Harpreet (International Journal of Engineering and Technology, 2019)
Traffic safety is a major challenge in the automotive industry. As vehicular ad-hoc networks (VANET) plays a vital role in road safety. Day by day the number of vehicles increases, which lead to road traffic and many other problems so to solve this there must be an efficient communication between the vehicles. In this paper, we study the existing address configuration and propose a scheme for efficient communication in vehicular networks.Â Â Â